PENGEMBANGAN APLIKASI GAMELAN SELONDING BERBASIS ANDROID - I Putu Nata Susila; I Gede Mahendra Darmawiguna; I Made Gede Sunarya (Universitas Pendidikan Ganesha, 2015)
Gamelan selonding are one of Balinese musical instrument that still use iron as their lath. Gamelan selonding use 8 laths that were hanged down on their ‘pelawah’. Gamelan selonding is played by using two ‘panggul’ that were made from wood. Selonding is gamelan that has 7 tones. Selonding it self contain 5 that is ‘peanem petuduh’, ’nyongnyong ageng’, ‘nyongnyong alit’, ‘kempur’ and one ‘gong’. The objective of this research was to design an application about gamelan selonding base on android, 2 to implemen the design of the application gamelan selonding based on android.This application were developed by using Waterfall Method that was implemented in JAVA language program by using Eclipse as editor and AndEngine as a add on library. The main feature of this application is to play selonding instrument. Besides that the developer also add another feature which is train to selonding and the tutorial video about how to play selonding. At the end developer hope that selonding are getting well known by people.The result of this study is Gamelan Selonding Based on Android. Features that deserved in this application are Selonding virtual instrument, lesson of playing one of the basic Selonding instrument, and also video of how to play Selonding in reality. All of fungtional needed was already implemented appropriate with the design succesfully.